Btn2a2 Regulates ILC2–T Cell Cross Talk in Type 2 Immune Responses - Frech, Michael; Omata, Yasunori; Schmalzl, Angelika; Wirtz, Stefan; Taher, Leila; Schett, Georg; Zaiss, Mario M.; Sarter, Kerstin (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILC) are not only responsible for shaping the innate immune response but also actively modulate T cell responses. However, the molecular processes regulating ILC-T cell interaction are not yet completely understood. The protein butyrophilin 2a2 (Btn2a2), a co-stimulatory molecule first identified on antigen-presenting cells, has a pivotal role in the maintenance of T cell homeostasis, but the main effector cell and the respective ligands remain elusive. We analyzed the role of Btn2a2 in the ILC-T cell cross-talk. We found that expression of Btn2a2 is upregulated in ILC2 following stimulation with IL-33/IL-25/TSLP. In vitro and in vivo experiments indicated that lack of Btn2a2 expression on ILC2 resulted in elevated T cell responses. We observed enhanced proliferation of T cells as well as increased secretion of the type 2 cytokines IL-4/IL-5/IL-13 following co-cultures with Btn2a2-deficient ILC2. In vivo transfer experiments confirmed the regulatory role of Btn2a2 on ILC2 as Btn2a2-deficient ILC2 induced stronger T cell responses and prevented chronic helminth infections. Taken together, we identified Btn2a2 as a significant player in the regulation of ILC2-T cell interactions.